How can dialogue journal writing improve learners' writing performance in the English as a second language context? - Foroutan, Maryam; Noordin, Nooreen; Hamzah, Mohd. Sahandri Gani (International Organization Of Scientific Research, 2013)
This paper compared the effect of two different methods in writing including dialogue journal writing (DJW) and Topic -Based writing (TBW) on the overall writing performance based on categories, content, organization, vocabulary, language use, and mechanics. In this quasi-experimental study, forty intermediate English students at a Malaysian university participated. TBW group (n=20) received conventional writing instruction through which teacher corrected and provided feedback on students’ writing tasks explicitly, while DJW group (n=20) applied dialogue journal writing through which the teacher provided feedback indirectly by rewriting the sentences and handing the students some examples compiled in the handouts. The quantitative research findings suggest that each writing method can be applied by writing instructors to assist their learners on different writing tasks. Implications of the study will be discussed based on the findings reported.